Public services and the European union healthcare, health insurance and education services - Nistor, Laura (Legal issues of services of general interest., 2011)
Patients travelling abroad to receive medical treatment, healthcare providers wishing to establish their seat or to provide services abroad, and students travelling abroad for education were faced with different barriers which have been declared illegal by the Court of Justice of the European Union. Member States started to use market mechanisms in their welfare systems and this triggered the application of the European internal market and competition rules. Fears related to whether all these would endanger the well-functioning of the welfare services have been raised by Member States. Several conflicts took shape: between national social interests and European Union economic interests; between individual interests and national general interests; between regulation and deregulation, centralization and decentralization. The author shows that behind those fears actually protectionist measures are hidden and that the European Law provides sufficient safeguards for the national welfare systems. In particular academia professionals and practitioners will benefit from the approach taken in this book.